(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides brief information about the phenomenological structure of emotional experience. The development of the study of emotions, thoughts on the psychophysiology of emotions from the point of view of modern linguistics are also presented. One of the factors influencing a person’s speech in the speech process is his cultural affiliation with a particular ethnic group, culture and how this affects his emotional experiences and manifestations. It also provides detailed information about the unique emotional language of the Uzbek, Russian and English-speaking peoples, how they communicate and express it to the people around them.